New fraud diamond theory: Why people commit fraudulent financial statements? - Rahman, Arief; Sarundayang, Jenneka Ika (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study examines the determinants of fraudulent financial statements in Indonesia’s non-bank financial industry by integrating the New Fraud Diamond Theory with Agency Theory. Specifically, it investigates the roles of financial targets, nature of industry, earnings management, and changes in directors as proxies for motivation, opportunity integrity, and capability, respectively. Using a quantitative approach, this study analyzes panel data from 53 non-bank financial institutions listed on the Indonesia Stock Exchange over the 2019-2022 period, yielding 212 firm-year observations. Fraudulent financial statements are measured using the Beneish M-Score model, while hypothesis testing is conducted through fixed-effects panel regression analysis. The empirical results indicate that financial targets, nature of industry, and earnings management significantly increase the likelihood of fraudulent financial reporting, whereas changes in directors do not exhibit a significant effect. These findings suggest that fraudulent financial statements are primarily driven by incentive pressure, discretionary accounting environments, and weakened managerial integrity rather than by leadership turnover. From an agency perspective, aggressive performance targets and information asymmetry intensify characterized by high estimation uncertainty. This study contributes to the fraud literature by providing empirical support for the New Fraud Diamond Theory in the context of non-bank financial institutions and highlights the critical role of integrity in translating pressure and opportunity into fraudulent behavior. The results offer practical implications for auditors, regulators, and investors in strengthening fraud risk assessment, ethical governance, and financial reporting oversight.